2021
DOI: 10.1111/hae.14336
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐guided prophylaxis improved clinical outcomes in paediatric patients with severe haemophilia A

Abstract: Background The traditional weight‐based dosing regimen can lead to under‐ or overdosage due to the interindividual variability of pharmacokinetic (PK) parameters. PK‐guided prophylaxis can be an optimized therapy choice. Aim This study aimed to investigate the clinical outcomes of PK‐guided prophylaxis in 46 boys with severe haemophilia A. Methods Forty‐six boys with severe haemophilia A were enrolled in Beijing Children's Hospital. The PK tests were performed using a five‐point assay. PK parameters were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…Urgent request of a higher trough level was also revealed by the low zero bleeding proportions of different trough level groups at study entry. This was in accordance with other well conducted studies before 20,21 . During the individualised prophylaxis period, the most escalations (59.6%) were due to the joint bleeds alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Urgent request of a higher trough level was also revealed by the low zero bleeding proportions of different trough level groups at study entry. This was in accordance with other well conducted studies before 20,21 . During the individualised prophylaxis period, the most escalations (59.6%) were due to the joint bleeds alone.…”
Section: Discussionsupporting
confidence: 92%
“…This was in accordance with other well conducted studies before. 20 , 21 During the individualised prophylaxis period, the most escalations (59.6%) were due to the joint bleeds alone. But if joint bleed is the only criteria for escalation, dose adjustment would not have been performed in the remaining 40.6% in lack of systematical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial differences in PK profiles lead to FVIII dosing discrepancies compared with traditional fixed dosing regimens. 11,12,18,[23][24][25][26][27] The median t 1/2 observed in our study was similar to the half-life of Koate-DVI reported in the published data from Grifols (16.13 h). 28 The t 1/2 in our study would differ if a different concentrate was used.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to those of other studies that evaluated the PK profiles of HA patients on prophylaxis with a standard regimen or LDP of FVIII. The substantial differences in PK profiles lead to FVIII dosing discrepancies compared with traditional fixed dosing regimens 11,12,18,23–27 …”
Section: Discussionmentioning
confidence: 99%
“…PK analysis was performed by Web-Accessible Population Pharmacokinetic System (WAPPS-Hemo). A five-point assay was utilized (Pre-dose, 1 h, 9 h, 24 h, 48 h) (10). FVIII levels were determined by one-stage assay.…”
Section: Pk Evaluation and Fviii Level Calculationmentioning
confidence: 99%